The Role of Digital Learning Media in Improving the Quality of Geography Learning: A Review - Susan E Manakane; Rakuasa, Heinrich (Journal Education Innovation (JEI), 2023)
This research discusses the role of digital learning media in improving the quality of geography learning through a comprehensive review of related issues. Digital learning media has brought significant changes in education, particularly in the context of geography, by providing interactive, visualization and personalization tools that enrich students' learning experience. This research uses a descriptive qualitative approach. The type of research used is a literature study which is research that has been done before by collecting journal books, magazines, and scientific papers that are interrelated with the problems and research objectives. The results of the review show that the utilization of digital learning media can strengthen the understanding of geography concepts, encourage more active student involvement, and assist in the development of problem-solving skills. However, challenges such as technology accessibility and teacher training still need to be addressed. Thus, this study concludes that the use of digital learning media has great potential in advancing geography education, but needs to be accompanied by appropriate strategies and support to optimize its benefits in improving the quality of geography learning in the future